The impact of service tax on spending behaviour intention of consumers in Perak, Malaysia - Lim, Ying Tong (2024)
The Malaysian government's decision to increase service tax from six percent to eight percent starting 1st March 2024, has boosted interest in understanding its impact on consumer behaviour in Perak, Malaysia. This study employs the Theory of Planned Behaviour (TPB) to investigate the relationship between attitude, subjective norm, perceived behavioural control, service tax awareness, and spending intention under service tax 2.0. Through a quantitative approach, 100 questionnaires were distributed to consumers in Perak via Google Forms, and the data were analysed using IBM SPSS Statistics. Results reveal that all the independent variables account for 68.7% of the variance in consumer spending intention. Attitude and perceived behavioural positively influence spending intention under service tax 2.0, while subjective norm and service tax awareness do not exhibit significant effects on spending behaviour intention among consumers in Perak. These findings underscore the importance of attitude and perceived behavioural control in shaping consumer spending intentions under service tax 2.0. Policymakers should prioritize fostering positive attitudes among consumers and enhancing perceived behavioural control of consumers to successfully implement the new service tax policy. By focusing efforts on these areas, policymakers can ensure better perception and smoother implementation of service tax changes, ultimately benefiting both consumers and the government regarding revenue collection and economic stability. This study contributes valuable insights into the dynamics of consumer behaviour in response to changes in service tax policy, offering practical implications for policymakers and businesses to consider when formulating strategies and communicating with consumers. It emphasizes the need to provide a user-friendly system for consumers to easily pay service tax while strengthening consumers' perceived behavioural control over the service tax and fostering positive attitudes towards it. Overall, the findings provide practical advice for policymakers and businesses aiming to enhance consumer reactions to the implementation of service tax 2.0 in Perak, Malaysia.